Deviation between willingness and actual behavior regarding community participation in protected areas: A case study in Shengjin lake national nature reserve in China - Wu, Tianyu; Jia, Weiguo; Wang, Qianwen (Frontiers in Environmental Science, 2023)
The deviation between high willingness and poor actual behaviors in community participation has become an obstacle to achieving effective management and resource protection of protected areas. Therefore, it is necessary to investigate this deviation and its influencing factors. Based on a field survey of community residents in the Shengjin Lake National Nature Reserve (SJLNNR) in Anhui Province, China, this study uses a Logistic-ISM model to analyze the key factors influencing the deviation and the hierarchical structure supporting those key factors. Resident members refer to those who live at home for six months or more during a calendar year. The results indicate that there is a significant deviation between participation willingness and actual behavior in SJLNNR. Furthermore, this deviation is characterized by eight key factors. Among these, awareness of the necessity of establishing SJLNNR is a direct factor at the surface level. Participation of important or recognizable people; average annual family income; understanding of environmental protection laws and regulations; realization of environmental improvement effect; satisfaction with SJLNNR authority; and future earnings expectations are all intermediate indirect factors. Furthermore, resident member is a fundamental factor. Finally, this study provides policy implications for converting willingness into actual participation in the community and promoting sustainable development.